Experiences of women living with borderline personality disorder - N. Ntshingila; M. Poggenpoel; C. P.H. Myburgh; A. Temane (AOSIS, 2016)
There is limited understanding of the experiences of women living with borderline personality disorder. It was therefore decided to discover how women living with this disorder would tell their life story. For the researcher, who worked in a psychotherapy ward where most women were living with borderline personality disorder, the care of these women was of vital importance, as they were less understood by mental health care providers.The research aimed to explore and describe the experiences of women living with borderline personality disorder. A qualitative, explorative, descriptive and contextual study design was used. Data was collected through in-depth phenomenological interviews that focused on the central question, "Tell me your life story". Eight participants living with borderline personality disorder were interviewed. Tesch's method for data analysis was used (Creswell, 2009:186), along with an independent coder. Measures to ensure trustworthiness and ethical principles were applied throughout the research. From the findings obtained by means of the interviews of women living with borderline personality disorder, it was evident that there were childhood experiences of living in an unsafe space, related to unhealthy family dynamics, boundary violations and educational challenges. They experienced chronic feelings of emptiness in their relationships with theself. They also presented with a pattern of unstable interpersonal relationships and compromised mental health, which was apparent through the early on set of mental problems, emotional upheaval, looking for emotional escape and having different triggerfactors. Lastly, all these women yearned for facilitated mental health.